Los fundamentos de la responsabilidad civil en el consentimiento informado - Montero Ordinola, Gustavo E. (2020)
Paternalism justified for centuries the meddling of the doctor in the patient’s will. The conception of the rational and moral man, alongside the scientific advances of the 20th century gave rise to the rights of the patient and bioethics, one of the pillars of which being the informedconsent. The purpose is to determine the grounds of civil liability for its infringement, which justifies a review of the historical support thatled to the self-determination of the patient.